Axel Leijonhufvud: A personal recollection from an Austrian perspective - Carmelo Ferlito; Axel Leijonhufvud (PSL Quarterly Review, 2022)
Professor Axel Leijonhufvud passed away few months ago, at the age of 89. Despite the fact that the contribution he made to economics has been widely recognized, his approach remains 'problematic' because of his dialogue and proximity with different streams of thought, and in particular with the Austrian School. This short recollection, developed from an Austrian perspective, touches only briefly on Leijonhufvud's hybrid interpretation of the Great Recession. More space is instead devoted to analysing his institutional approach to the phenomenon of inflation and its link with monetary policy and monetary regimes. Some reflections are focused on the importance of microfoundations and of studying the market process as a process of inter-temporal coordination, with a final call for humility within the economics profession.
Keywords: B31; B32; B40; B53; B59; E12; E14; 330; Axel Leijonhufvud; obituaries; Neo-Keynesian economics; Austrian School of Economics; disequilibrium; inflation